2019
DOI: 10.1177/2324709619852760
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Multiple Myeloma Presenting as Evan’s Syndrome

Abstract: Multiple myeloma is defined as the neoplastic proliferation of plasma cells resulting in a monoclonal gammopathy. The classic presentation of a patient is someone who presents with bone pain, osteopenia, or new onset fractures. We present a case of multiple myeloma presenting as Evan’s syndrome (ES). Evan’s syndrome is autoimmune hemolytic anaemia with autoimmune thrombocytopenia. A 44-year-old female was referred from her primary physician to the hospital as laboratory testing revealed haemoglobin of 5 gm/dL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The concurrence of Evan’s syndrome with proteinuria is relatively infrequent. However, it has been reported previously along with other comorbidities [ 37 , 38 ]. Three Evan’s syndrome patients died of large intracranial haemorrhage (ICH) and one due to pulmonary embolism [ 6 ].…”
Section: Immune Thrombocytopenia and Autoimmune Diseasesmentioning
confidence: 81%
“…The concurrence of Evan’s syndrome with proteinuria is relatively infrequent. However, it has been reported previously along with other comorbidities [ 37 , 38 ]. Three Evan’s syndrome patients died of large intracranial haemorrhage (ICH) and one due to pulmonary embolism [ 6 ].…”
Section: Immune Thrombocytopenia and Autoimmune Diseasesmentioning
confidence: 81%
“…40  Case reports of multiple myeloma with Evans syndrome There have been case reports of ES associated with MM. [41][42][43][44][45][46] All reported cases had IgG subtype. A previous study demonstrated that among AIHA patients associated with MM, the subclass of the antibody binding to RBC was fully linked with that of M protein in all patients.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…Patients still have a high possibility of recurrence after complete remission [ 3 , 4 ], so that the system of recurrence prediction is very important in the prevention and treatment of MM. According to the immunoglobulin types secreted by myeloma cells, MM is divided into Ig A type, Ig G type, Ig M type, and light chain type in clinic, and further divided into κ type and λ type according to light chain type [ 5 , 6 ]. There are differences in the secretion levels of immune factors and inflammatory factors in patients with different immune classifications, but patients can still find the same markers to evaluate the prognosis; for example, Dong Yi et al have found that the expression of p53 protein, bcl-2 protein, and soluble interleukin-2 receptor (sIL-2R) in patients with MM at the first diagnosis and subsequent visit is positively correlated with β 2 -microglobulin ( β 2 -MG), speculating that p53 protein, bcl-2 protein, and sIL-2R can be used to predict the recurrence of MM [ 7 ].…”
Section: Introductionmentioning
confidence: 99%